PELAKSANAAN PEMBUATAN AKTA AUTENTIK OLEH NOTARIS DI KABUPATEN LIMA PULUH KOTA - Umul Khair (Ensiklopedia Social Review, 2021)
Notaries are public officials authorized to make authentic deeds and other authorities. Meanwhile, agreements made in writing before a notary or government official have perfect evidentiary power. Implementation of Authentic Deed Making by a Notary in Fifty Cities District the parties/appearers come to consult with the notary's office of consultation and convey what they want, the notary explains everything to the parties/appearers if everything has been completed by the parties/appearers, the deed will be signed by the parties (minuta/deed) and a copy will be issued by a notary, so based on the research the author did on the implementation of making an authentic deed by a notary in the District of Fifty Cities, it was in accordance with the Standard Operating Procedure (SOP), but was not maximized due to several obstacles. namely: the parties/appearers who came to the notary's office did not understand the notary deed and thought that the cost of making a notary deed was high and because the management system was on line, both CV, PT and Foundation, when the network had problems, the timing did not match the initial predictions of the parties. The solutions are as follows: increasing the understanding of the parties/appearers about the authentic deed, providing explanations to the parties/appearers about the procedure for making a notarial deed, explaining to the parties/appearers who come to the notary's office and changing the mindset and assumptions of the parties/appearers regarding the cost of making a notarial deed is high as well as providing explanations and understanding to the parties/appearers because the management system is online, when the network is in trouble, the time is not in accordance with the initial predictions of the parties/appearances. The suggestions are as follows: that the notary must be more careful in examining and making the deed, it is hoped that it will be a comprehensive renewal and reorganization in a law that regulates the position of a notary so that legal knowledge is created that applies to all residents throughout the territory of the State of Indonesia.Keywords: Implementation, Making, Authentic Deed, Notary.